Investigation of pre and post plating surface roughness of electroless nickel phosphorus coated substrate for diamond turning application - Xia, Peter; Almond, Heather; Impey, Susan A. (European Society for Precision Engineering and Nanotechnology, 2016)
In an overarching project to reduce the number of defects found in electroless nickel phosphorus alloy (EN-P) coatings on large diamond-turned components used in the next generation of reel-to-reel (R2R) printing stations, the significance of the coating surface on achieving a wear resistant and optically smooth surface has been investigated. This paper presents an investigation that focuses on the substrate roughness variation achieved through different pre-treatment methods prior to coating using a commercial plating solution. It looks at the number of features observed pre and post plating. The results provide some suggestions with respect to the diamond machining of a 100 micron thick EN-P coating.
Keywords: Electroless nickel; nickel phosphorus alloy; EN-P; surface feature; defects; pre-treatment; diamond turning